THE ROLE OF DIGITAL MARKETING IN INCREASING SALES TURNOVER FOR MICRO, SMALL, AND MEDIUM ENTERPRISES - Saut Maruli Tua Pandiangan; Cut Susan Octiva; Muhammad Yusuf; Suryani Suryani; Revi Sesario (JURNAL PENGABDIAN MANDIRI, 2022)
The purpose of this community service activity is to socialize the role of digital marketing in increasing sales turnover for Micro, Small, and Medium Enterprises (MSMEs). Based on the problems found and formulated, the problem solving framework carried out through this community service activity is to socialize the use of digital marketing in order to help increase sales turnover to MSMEs. In this socialization, the authors target MSMEs actors as learning digital marketing. The implementation of community service socialization activities is carried out using lecture, tutorial, and discussion methods. This socialization activity is very beneficial for MSMEs who have small businesses. The material provided can also add to the understanding of knowledge and practice of using Facebook or Instagram for product promotion. Through this socialization activity, it is hoped that it will increase the awareness of MSMEs community in Gaharu Village, Medan Timur District, Medan City, North Sumatra Province to start practicing the use of Facebook or Instagram for product promotion. It is hoped that MSMEs actors can share knowledge about using Facebook or Instagram for product promotion to other MSMEs actors. It is also hoped that the organizing committee will be able to organize socialization activities with topics related to other MSMEs so that they can be explored and practiced in the world of MSMEs.